Urban livelihoods and the risk of HIV infection: lived experiences of young migrant women in Havana informal settlements in Windhoek, Namibia - Shinana, Eveline M (My University, 2014)
Informal settlements are associated with higher prevalence of HIV. There is empirical evidence that HIV prevalence is higher in the North-Western suburbs (Katutura) of Windhoek which primarily consist of low-income housing and informal settlements. It is reported that a large proportion of young women in these suburbs who are 25 years and younger are HIV positive. This study sought to explore the linkage between urban livelihood strategies and the risk of acquiring HIV among young migrant women (aged 18 to 24) in Havana informal settlement in Katutura in Windhoek, Namibia. The study focuses on the lived experiences of internal young migrant women to explore the linkage between their livelihood strategies and the risks of acquiring HIV. A desk review was undertaken in order to analyse existing documents related to urban livelihoods and HIV from studies that have been conducted in the City of Windhoek. Semi-structured interviews and focus group discussions as research instruments were administered to collect primary data. Thematic analysis has been employed to analyse the data to help extract descriptive information concerning experiences of young migrant women in Katutura informal settlements and construct meanings in order to be able to understand how livelihood strategies of young internal migrant women in Havana relate to the risk of acquiring HIV. The study reveals that young migrant women in Havana informal settlement moved to Windhoek in order to have their livelihoods improved. Based on the data, income; education; employment and housing are some of the social and economic factors found to be affecting the livelihoods of the young migrant women. Furthermore, the study unveils that young migrant women engage in risky sexual behaviours such as low condom use, transactional sex and multiple concurrent partnerships as a strategy to earn livelihoods. Engaging in risky sexual behaviour such as transactional sex enhances the risk of acquiring HIV once they are exposed, as it influences their sexual decision making due to their dependency on men. The study concludes that there is a linkage between urban livelihoods and the risk of HIV infection. Therefore, exclusion of migrant communities from services as well as their limited access to sustainable livelihoods encourages young migrant women to engage in risky sexual behaviour. The findings of this study do not portray that all young women in Havana informal settlement engage in risky sexual behaviour because young migrant women are a heterogeneous group however, participants who took part in this study are a representative of all young migrant women (aged 18-24) in Havana. Therefore, their risky behaviour can be one of the major factors contributing to high prevalence of HIV among young women in Katutura. KEY WORDS: Migration, HIV, risky sexual behaviour, urbanisation, livelihoods, informal settlements, urban poverty, Havana, Katutura, Windhoek